Impacts of Land Use and Land Cover Change on Soil Erosion and Hydrological Responses in Ethiopia - Ajanaw Negese (Applied and Environmental Soil Science)
Land use and land cover (LULC) dynamics, in general, and the conversion of the natural vegetation cover into cultivated land, in particular, are major human-induced problems in Ethiopia, which have played a significant role in increasing the rate of soil erosion and altering the hydrological balance in the country. The main aim of this review was to view previous studies in Ethiopia that quantify the change in the rate of soil erosion and hydrological responses as a result of the change in land use and land cover in the country. From the past researches reviewed in this paper, the expansion of cultivated land at the expense of forest land, shrubland, and grassland in Ethiopia has increased the mean rate of soil erosion, sediment yield, surface runoff, mean wet monthly flow, and mean annual stream flow in the last four decades. On the other hand, the change has reduced the dry average monthly flow, groundwater recharge and groundwater flow, and evapotranspiration (ET) in the country. Future research works should pay more attention to the investigation of the impacts of land use and land cover change on groundwater hydrology and the prediction of future soil loss and hydrological imbalance under the changing land use and land cover in the country since little information is available from past researches on these issues. Research works are also required in lowland arid and semiarid areas in Ethiopia to effectively manage soil and water resources in all parts of the country.